2020
DOI: 10.3389/fimmu.2020.00058
|View full text |Cite
|
Sign up to set email alerts
|

Osteoimmunology: A Current Update of the Interplay Between Bone and the Immune System

Abstract: Immunology, already a discipline in its own right, has become a major part of many different medical fields. However, its relationship to orthopedics and trauma surgery has unfortunately, and perhaps unjustly, been developing rather slowly. Discoveries in recent years have emphasized the immense breadth of communication and connection between both systems and, importantly, the highly promising therapeutic opportunities. Recent discoveries of factors originally assigned to the immune system have now also been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 224 publications
(240 reference statements)
0
95
0
2
Order By: Relevance
“…Besides the small molecules mentioned above, LZ-8, first FIP family protein isolated from G. lucidum (Kino et al, 1989), functioned as immune modulator in immune cell and cancer cell (Haak-Frendscho et al, 1993;Huang et al, 2009). Accumulating evidences in osteoimmunology field suggested that immune modulation was a promising anti-osteoporosis strategy (Tsukasaki and Takayanagi, 2019;Guder et al, 2020). Therefore, we hypothesized that LZ-8 might affect osteoporosis through immune modulation.…”
Section: Discussionmentioning
confidence: 96%
“…Besides the small molecules mentioned above, LZ-8, first FIP family protein isolated from G. lucidum (Kino et al, 1989), functioned as immune modulator in immune cell and cancer cell (Haak-Frendscho et al, 1993;Huang et al, 2009). Accumulating evidences in osteoimmunology field suggested that immune modulation was a promising anti-osteoporosis strategy (Tsukasaki and Takayanagi, 2019;Guder et al, 2020). Therefore, we hypothesized that LZ-8 might affect osteoporosis through immune modulation.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that activated T cells play an important role in bone health and disease. Especially, Th17 cells have a great influence on bone metabolism by secreting characteristic soluble factor that induces osteoclastogenesis [ 35 ]. In contrast, effector T cell production of IFN- γ strongly suppresses bone resorption by interfering with the RANKL/RANK signaling pathway [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different signaling pathways of these and other cells of the immune system regulate their function and bone remodeling (25)(26)(27)(28)(29) (Figure 2). Indeed, the bone and the immune system maintain a close relationship both anatomicalsince the bone houses the bone marrow-and functional through different molecular and cellular signaling pathways and a myriad of cytokines (25,26,28,29). Accordingly, osteoimmunology is a discipline that attempts to address all these interrelations (30) and has undergone a great development in recent years.…”
Section: Bone Homeostasis and Bone Remodeling And The Immune Systemmentioning
confidence: 99%
“…They are proteins belonging to the TNF superfamily. RANKL is expressed, both soluble and membrane-bound forms, in different bone cells (osteoblasts and osteoclasts) and also in different cell subsets of the immune system (25,28,29). By contrast, RANK is mainly expressed in osteoclasts.…”
Section: Increased Bone Resorption In Ramentioning
confidence: 99%